Penerapan Strategi Pemasaran pada Toko Laris dalam Meningkatkan Volume Penjualan - Eni Nuraeni Ruriawati; Eben Sahlan; Ali Khairudin; Adi Indradi Wazdi (Jurnal Maps (Manajemen Perbankan Syariah), 2022)
The growing business world which includes the trading industry, one of which is a modern shop company or mini market/supermarket which is now very easy to find in the community. The spread of mini markets in the community creates competition for business actors. One of the provinces in Indonesia, namely West Java, has quite a number of modern shops or mini markets. Toko Laris is one of the newly established mini markets in West Java, precisely in Kedawung District, Cirebon Regency. In addition to the competition with other mini markets that Toko Laris has to deal with, the Covid-19 pandemic is also a challenge not only for Toko Laris but also for all other business actors in increasing their sales volume. The purpose of this study is to analyze and identify the application of marketing strategies at the Laris Store in increasing its sales volume, analyze the factors that influence the marketing strategy, and analyze the marketing strategy at the Laris Store in terms of Islamic economics. The research method used is mixed methods, namely methods that combine qualitative and quantitative approaches. The types of data used are primary and secondary data with research instruments guiding observations, interviews, and documentation. The technique of determining the resource persons uses non-probability sampling, namely the head of the shop and the consumers of Toko Laris with a judgment sampling technique. The data analysis used is SWOT analysis and data validity test using triangulation method. The rsesult of this research is that the marketing strategy applied by Toko Laris is using the 4Ps consisting of product (product), price (price), place (place/distribution), and promotion (promotion). The promotion strategy has not been maximally implemented by Toko Laris, which is one of the factors that affect the level of sales. Judging from the Islamic economy, the marketing strategy applied by Toko Laris is still within the corridor of sharia and nothing deviates from Islamic teachings, for example, Toko Laris does not sell illicit products and does not take profits beyond reasonable limits.